Clinical patterns of metabolic syndrome in young, clinically stable, olanzapine-exposed patients with schizophrenia - Jun Ma; Lin Zhang; Zhengyuan Huang; Gaohua Wang (Annals of General Psychiatry)
Abstract Background Schizophrenia (SCZ) is a chronic, disabling mental illness with a high disease burden and is often comorbid with metabolic syndrome (MetS). The aim of this study was to determine the prevalence of MetS in young, clinically stable, olanzapine-exposed patients with SCZ and to explore predictive factors affecting the development and severity of MetS. Methods A total of 274 patients with SCZ who met the inclusion criteria were enrolled in this study, and their demographic data and general clinical information were collected. Concurrently, patients were assessed for psychopathology, illness severity, and antipsychotic drug–related adverse effects. Results The prevalence of MetS in the target population was 35.77%, and the MetS subtype of abdominal obesity + high triglycerides + low level of high-density lipoprotein cholesterol accounted for the majority of patients in the MetS subgroup. Binary logistic regression showed that body mass index (BMI), uric acid (UA), thyroid-stimulating hormone, and QT-c interval could significantly and positively predict the development of MetS. Multiple linear regression showed that olanzapine concentration, BMI, and UA could significantly and positively predict higher MetS scores. Conclusion This study reports the clinical patterns of MetS in young, clinically stable, olanzapine-exposed patients with SCZ and identifies the correlations influencing the development and severity of MetS. These findings could potentially be applied toward the prevention of and intervention in MetS.